Investigations in the workplace - Ferraro, Eugene (CRC Press, 2012)
The process of investigation is dynamic and fluid. The approach must be reasonable and the investigator flexible. However, in order to be successful, every investigation must have a meaningful purpose and be executed ethically and lawfully. Inevitably, employers must invest time, money, and patience to ensure they obtain demonstrable and actionable results. To achieve this and reduce the exposure to unnecessary business disruptions and litigation, every workplace investigation must by driven by process. Investigations in the Workplace, Second Edition provides both novice and experienced invest.